Business Cycle and Public Health: The Moderating Role of Health Education and Digital Economy - Zhang, Xing; Xu, Yingying (Frontiers in Public Health, 2022)
Cyclicality of public health in emerging market is underexplored in existing literature. In this study, we used a fixed effect model and provincial data to document how public health varies with the business cycle in China over the period of 2010-2019. The estimated results showed that business cycle is negatively correlated with the mortality of infectious disease, a proxy variable of public health, thus indicating that public health exhibits a countercyclical pattern in China. Furthermore, we investigated the potential moderating role of public health education and digital economy development in the relationship between business cycle and public health. Our findings suggested that public health education and digital economy development can mitigate the damage of economic conditions on public health in China. Health education helps the public obtain more professional knowledge about diseases and then induces effective preventions. Comparing with traditional economic growth, digital economy development can avoid environmental pollution which affects public health. Also, it makes the state-of-the-art medical services available for the public through e-health. In addition, digitalization assures remote working being practicable and reduces close-contact during the epidemics such as COVID-19. The conclusions stand when subjected to several endogeneity and robustness checks. Therefore, the paper implicated those improvements in public health education and digitalization benefits the government in promoting public health.